Pengaruh Intangible Asset dan Aktivitas Riset terhadap Kinerja Perusahaan Serta Dampaknya terhadap Pergerakan Harga Saham: Studi pada Perusahaan Manufaktur yang Terdaftar di BEI - Bella Sindi Luvita Riyani; Rio Johan Putra (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
In Indonesian innovation organizations, this study takes a gander at how elusive resources and innovative work (Research and development) exercises influence organization execution and stock cost developments. This topic is important because innovation and intangible assets are important in the knowledge-based economy era. Using a quantitative procedure with the model are creating associations recorded on the IDX, this study looks at data from financial plan outlines, through and through gatherings, and company reports. The findings demonstrate that the organization's stock cost and presentation are significantly influenced by immaterial resources. The organization's presentation and stock cost are unaffected by research projects, which is unusual. The stock price itself has a significant impact on the company's performance in the interim